Annual Plant Reviews Online 2021
DOI: 10.1002/9781119312994.apr0740
|View full text |Cite
|
Sign up to set email alerts
|

The Cream of the Crop: Biology, Breeding, and Applications ofCannabis Sativa

Abstract: Cannabis sativais an extraordinarily versatile species. Hemp and its cousin marijuana, bothC. sativa, have been used for millennia as a source of fibre, oil, and for medicinal, spiritual, and recreational purposes. Because the consumption ofCannabiscan have psychoactive effects, the plant has been widely banned throughout the last century. In the past decade, evidence of its medicinal properties did lead to the relaxation of legislation in many countries around the world. Consequently, the genetics and develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 246 publications
0
9
0
Order By: Relevance
“…Hemp ( Cannabis sativa ) is a highly versatile crop with dozens of different applications, ranging from the fibres that can be manufactured into textiles and ropes to the highly nutritious seeds that can be processed into oil for human consumption. In addition, hemp has high carbon sequestration potential when used as insulation material (Ingrao et al., 2015 ; Schilling et al., 2021 ), and when utilized as a biofuel, hemp can act as a source of green carbon and renewable energy (Ahmed et al., 2022 ). The beneficial effects of non‐hallucinogenic cannabinoids like cannabidiol (CBD) are being analysed for the treatment of various diseases, such as anxiety and depression, Parkinson's disease, epilepsy and different types of cancers (Schluttenhofer & Yuan, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Hemp ( Cannabis sativa ) is a highly versatile crop with dozens of different applications, ranging from the fibres that can be manufactured into textiles and ropes to the highly nutritious seeds that can be processed into oil for human consumption. In addition, hemp has high carbon sequestration potential when used as insulation material (Ingrao et al., 2015 ; Schilling et al., 2021 ), and when utilized as a biofuel, hemp can act as a source of green carbon and renewable energy (Ahmed et al., 2022 ). The beneficial effects of non‐hallucinogenic cannabinoids like cannabidiol (CBD) are being analysed for the treatment of various diseases, such as anxiety and depression, Parkinson's disease, epilepsy and different types of cancers (Schluttenhofer & Yuan, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…To date, modern clinical studies that have investigated the medicinal properties of cannabis substances have focused primarily on the pharmacological potential of single cannabinoids to treat specific medical disorders [ 31 , 32 ], such as CBD for palliative care of Parkinson disease [ 33 ] or THC for the suppression of nausea in patients with cancer who are undergoing chemotherapy treatments [ 34 ]. However, over the years, a large number of publications have indicated that the therapeutic effect of whole-plant-based remedies is often superior to the effect obtained from drugs containing a single purified cannabinoid.…”
Section: Introductionmentioning
confidence: 99%
“…Cannabis sativa L. is one of the earliest known cultivated plants, with archaeological records implying human use at least 8,000 years before present (Kovalchuk et al, 2020;Long et al, 2017). A multipurpose crop, the applications of C. sativa are significant, spanning biofuel, textiles, building materials and paper (Schilling et al, 2021). Additionally, as a fast-growing annual plant, C. sativa has the potential to aid carbon sequestration efforts (Finnan and Styles, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…However, C. sativa is best known for its medicinal and intoxicating applications, as glandular trichomes on female C. sativa flowers produce high-value, psychoactive compounds called cannabinoids (Livingston et al, 2020;Melzer et al, 2022). One of these cannabinoids, cannabidiol (CBD), is non-intoxicating with anti-cancer and anti-inflammatory effects, currently used to treat conditions like epilepsy and multiple sclerosis (Schilling et al, 2021).…”
Section: Introductionmentioning
confidence: 99%